Survival Rates of Endodontically Treated Teeth After Placement of Definitive Coronal Restoration: 8-Year Retrospective Study - Sadaf D (Dove Medical Press, 2020)
Durre Sadaf1,2 1Conservative Dentistry Department, College of Dentistry, Qassim University, Qassim, Saudi Arabia; 2Graduate Reading, Centre of Evidence-Based Medicine, University of Oxford, Oxford, UKCorrespondence: Durre Sadaf Email d.ahmad@qu.edu.saIntroduction: Preservation of endodontically treated teeth (ETT) depends upon several patient-related and operator-related factors. The objectives of this study were to assess the effects of different types of coronal restoration and delayed placement on ETT survival.Methods: Data on dates of root canal treatment (RCT), restoration type, and extraction time of tooth, when applicable, were analyzed for all patients who underwent RCT from 2010 to 2018 at our institution.Inclusion Criteria: Root canal-treated teeth with complete preoperative and postoperative radiographs; ETT that were restorable and received final permanent coronal restorations; no periodontal disease or crack detected during RCT; and ETT with acceptable RCT quality.Exclusion Criteria: Patients who did not attend for follow-up, those had incomplete information available about the coronal restoration, and those with periodontally compromised teeth were excluded. ETT that involved any procedural error were also excluded. The teeth were categorized according to whether they underwent definitive coronal restoration 0– 14 days, 15– 59 days, or 60+ days after RCT. The statistical analysis was performed using SPSS version 25 (IBM Corp., Armonk, NY). The rate of survival of ETT of 8 years was estimated, and the differences between groups were determined after applying Kaplan–Meier statistics and log-rank tests. A multivariate Cox regression test and Wilcoxon (Gehan) statistics were computed to analyze the influence of different variables. A P-value < 0.05 was considered as statistically significant.Results: The type of restoration, opposing dentition, presence of a post, and dentistry training (year 4 or 5 students) showed significant effects on the survival of ETT (P ≤ 0.000). ETT which received crowns was 2.05 times more likely to need extraction than those in which a composite buildup was performed (hazard ratio [HR] 2.05; confidence interval [CI] 1.84– 2.29; P ≤ 0.000). All composite buildups were performed within 14 days of completion of RCT. There was a significant correlation between the time of placement of the final coronal restoration and ETT survival (P ≤ 0.000). Extraction of ETT was 25% more likely (HR 0.25; CI 0.231– 0.277) when the final coronal restoration was placed 15– 59 days after completion of RCT and 73% more likely (HR 0.73; CI 0.655– 0.814) when placed after 60 days than when placed at 0– 14 days.Conclusion: Timely placement of the final coronal restoration is found to be the most critical factor affecting the long-term survival of teeth after RCT.Keywords: dental crown, endodontically treated teeth, root canal therapy, root canal treatment, survival analysis, survival rate